As ações de cuidado de profissionais de saúde implicados no Programa de Humanização do Parto - Maciel, Ana Maria Sá Barrêto (2012)
This research has the general objective of understanding the meanings of caring in the clinical action of health professionals inside a maternity in the countryside of Pernambuco who are involved in the Program for the Humanization of Childbirth (PHP). The studies have taken into account the conceptions of humanization, shelter and care defined by the program. Its specific objectives are: analyze the PHP of the Ministry of Health through the stated conceptions; describe the care methods of the health professionals who participate in the PHP and understand the meanings that they give to their professional clinical actions. It includes six (06) participants, all of them members of the staff of the referred maternity hospital. They received training and qualification to act for the Program for the Humanization of Childbirth. The methodology used includes a documentary investigation to research the conception of humanization that is at the root of the training provided to the teams who participate in the PHP. At a second moment, we have adopted the qualitative focus in an interventional clinical perspective from an existential phenomenological way of understanding. The cartographic method, which means designing and unveiling the research scenario and also the fields of studies followed by the researcher, was considered in this research. The tools used were the researcher's field diary and the testimonials (with starter question) of health professionals (subject collaborators). The consequent narratives, all of them substantiated as possibilities for development of lived experiences, were guided by texts of Benjamin (1999). As analysis procedure, it was taken into consideration the philosophical hermeneutics such as punctuated by Gadamer (2005). The narratives unveiled the guiding questions that of our research affects the participants deeply. The technical view which guide the reflections about how to conceptualize the care in clinical action and the construction of the biomedical model applied in childbirth care, in which the healthcare professionals are linked, are some of the themes present in the narratives of the participants. Thus, the research may contribute to that participants could thematize about the possibility of conceiving the man, the world and the science itself in other ways which the covered exclusively by the technical vision